2012
DOI: 10.1007/s10067-012-2061-x
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking lung syndrome masked by pleuropericarditis: a case report and review of the literature

Abstract: The purpose of this article is to present an unusual case of shrinking lung syndrome (SLS) masked by pleuropericarditis with a review of the literature. We report a case of SLS in a 44-year-old woman in which the diagnosis was initially confounded by concurrent pleuropericarditis. The English medical literature was comprehensively reviewed for SLS for its presentation, clinical findings, diagnosis, treatment, with specific focus on its pathogenesis. SLS is a rare respiratory complication associated with system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
2
1
4
Order By: Relevance
“…[16,48,51] Pleuritic chest pain is a prominent feature of patients with SLS. Our literature search revealed that 76% of SLS patients had active pleuritic chest pain at or shortly before clinical manifestation of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[16,48,51] Pleuritic chest pain is a prominent feature of patients with SLS. Our literature search revealed that 76% of SLS patients had active pleuritic chest pain at or shortly before clinical manifestation of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Aðrar kenningar hafa verið settar fram um mögulegan skort á lungnablöðruseyti (surfactant) með meðfylgjandi samfalli í lungnablöðrum (upphafleg kenning Hoffbrand og Beck), taugamein í n. phrenicus, almennt máttleysi í innöndunarvöðvum eða einhvers konar óútskýrða truflun í brjóst-veggnum. [3][4][5][6] Í þeim tilfellum sem lýst hefur verið hefur sterameð-ferð reynst gagnleg (prednisólón 20-80 mg/dag) en nýlegri rannsóknir sýna fram á gagnsemi rituximab (anti-CD20 mótefni). Ýmis önnur lyf notuð við rauðum úlfum, svo sem hydroxychloroqín, cyclofosfamíð og azathioprín hafa gefið misgóðan árangur.…”
Section: Vanishing Lungs -A Case Reportunclassified
“…Ýmis önnur lyf notuð við rauðum úlfum, svo sem hydroxychloroqín, cyclofosfamíð og azathioprín hafa gefið misgóðan árangur. 3,4,5,8 Samfara sterameðferð hafa verið reynd baeði theofyllín, sem talið er auka styrk þindarinnar, og β-2-örvandi lyf, sem minnka þreytu í þind í gegnum jákvaeð samdráttarhvetjandi (jónótróp) áhrif, og hvort tveggja gefið ágaetis árangur. 4 Tilfelli þetta sýnir glögglega hve mikilvaegt er að þekkja þessa sjúkdómsmynd þó sjaldgaef sé og kunna að beita réttri meðferð, ella er haetta á áframhaldandi framgangi sjúkdómsins með umtalsverðri skerðingu á lífsgaeðum.…”
Section: Vanishing Lungs -A Case Reportunclassified
See 2 more Smart Citations